A LATP solid electrolyte and a method for self-induced crystal growth thereof

In the synthesis process of LATP solid electrolyte, pure phase LATP seeds are used as the "seed" for solid phase crystal growth, and the raw materials are induced to spontaneously form pure phase LATP solid electrolyte, which solves the problems of high impurity phase content and unstable performance in the prior art, and achieves the needs of high performance, stability and large-scale production.

CN119750538AInactive Publication Date: 2025-04-04TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202510259133.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When synthesising LATP solid electrolytes, impurity phases are easily generated due to uneven raw material distribution and uneven sintering temperature control, resulting in impurity of crystal phase, low ionic conductivity, poor consistency and batch stability, making it difficult to meet the needs of high performance and large-scale applications.

Method used

Pure-phase LATP seeds are used as the 'seed' for growing solid-phase crystals. By mixing with lithium sources, aluminum sources, titanium sources and phosphorus sources, sintering is carried out to induce the raw materials to spontaneously form pure-phase LATP solid electrolytes, significantly reducing the impurity phase content and improving ionic conductivity and other properties.

Benefits of technology

It significantly improves the ionic conductivity, consistency and batch stability of LATP solid electrolytes, reduces the impurity phase content, has no obvious change in cost, has a high efficiency and cost ratio, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750538A_ABST
    Figure CN119750538A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials. The present invention provides a LATP solid electrolyte and a method for self-induced crystal growth thereof, the method comprising mixing pure phase LATP seed crystals, a lithium source, an aluminum source, a titanium source and a phosphorus source to obtain a mixed material; and then sintering the obtained mixed material to obtain the LATP solid electrolyte. By using pure phase LATP as a "seed crystal" for solid phase crystal growth during the mixing process, the raw material is induced to spontaneously form a pure phase LATP solid electrolyte, which significantly reduces the content of impurity phases, improves the ionic conductivity and other properties of the solid electrolyte, and effectively improves consistency and batch stability. Since the pure phase LATP seed crystal as an additive has the same composition as the target product, it will not introduce any impurities and can remain consistent before and after sintering. Therefore, the self-induced crystal growth method has a high cost-effectiveness ratio and has great technical prospects in the large-scale production process of LATP solid electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a LATP solid electrolyte and a method for self-induced crystal growth thereof. Background Art

[0002] Lithium-ion batteries have been widely used in vehicle power, energy storage grids, 3C electronic devices and other fields due to their advantages such as high operating voltage, high energy density and high cycle life. In order to further meet the market demand for lithium-ion batteries, it has become an imperative path to develop lithium-ion batteries with higher energy density, higher safety and higher cycle life. Among them, the semi-solid / quasi-solid / all-solid-state battery solution that uses solid electrolytes to completely or partially replace liquid electrolytes has become a research focus.

[0003] Among many solid electrolytes, LATP (lithium aluminum titanium phosphate) is a solid electrolyte with a fast ion conductor (NaSICON) structure, which has the advantages of low cost, good environmental adaptability, and high ionic conductivity. However, in the process of synthesis by the conventional method of solid phase mixing and sintering of powder materials, due to the uneven distribution of raw materials, uneven temperature control of the sintering section, and biased growth of product crystals, impurity phases such as AlPO4, TiP2O7, and LiTiPO5 are easily generated, resulting in impure crystal phases. These by-products generally have lower ionic conductivity (more than one order of magnitude lower than LATP), and their performance in other aspects such as crystal orientation and dispersibility also has large differences. Therefore, it is not conducive to the preparation of high-performance LATP solid electrolytes. In addition, different impurity phases will also lead to a decrease in the consistency and batch stability of LATP, which is not conducive to the large-scale application of LATP solid electrolytes. The route of liquid phase dispersion mixing and then drying and sintering is prone to segregation of raw materials, and it is also difficult to ensure the synthesis of high-purity and high-conductivity LATP solid electrolytes.

[0004] CN110265708A discloses a solid phase synthesis method for synthesizing a lithium lanthanum zirconium oxide solid electrolyte material with a garnet structure under the synergistic effect of a quaternary ammonium base. The scheme adopts a quaternary ammonium base-assisted method to react lithium carbonate to generate lithium hydroxide, and uses a quaternary ammonium base as a surfactant to promote the generation of LLZO pure phase. However, the additional additive quaternary ammonium base in the scheme is easily decomposed by heat, thereby generating ammonia and other toxic and harmful organic solvents, which is not conducive to the control of large-scale industrial production. At the same time, because the organic phase material is easily caused to produce carbon residues in LATP during incomplete sintering, the electronic conductivity of the solid electrolyte is too high, which in turn causes the problem of short circuit of the solid electrolyte.

[0005] Therefore, there is a need to propose a new method to ensure that high-purity LATP solid electrolyte can be synthesized in a more efficient way to improve its ionic conductivity and other performance, consistency and batch stability. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a LATP solid electrolyte and a method for self-induced crystal growth thereof, the method comprising mixing pure phase LATP seed crystals, a lithium source, an aluminum source, a titanium source and a phosphorus source to obtain a mixed material; sintering the obtained mixed material to obtain a LATP solid electrolyte. The present invention uses pure phase LATP as a "seed crystal" for solid phase crystal growth during the mixing process, inducing the raw material to spontaneously form a pure phase LATP solid electrolyte, significantly reducing the content of impurity phases, improving the ionic conductivity and other properties of the solid electrolyte, and effectively improving consistency and batch stability. At the same time, when the pure phase LATP seed crystal is used as an additive, it has the same composition as the target product, does not introduce any impurities, can remain consistent before and after sintering, and has no obvious change in cost. Therefore, the self-induced crystal growth method has a high cost-effectiveness ratio and has great technical prospects in the large-scale production process of LATP solid electrolytes.

[0007] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for self-induced crystal growth of LATP solid electrolyte, the method comprising: mixing pure phase LATP seed crystals, a lithium source, an aluminum source, a titanium source and a phosphorus source to obtain a mixed material; and sintering the obtained mixed material to obtain a LATP solid electrolyte.

[0008] The advantages of using pure-phase LATP seeds as additives for self-induced crystal growth in the present invention include: providing "seeds" for the initial growth of crystals, inducing the generation of LATP crystals, effectively reducing the generation of impurities, and improving ionic conductivity; using pure-phase LATP seeds as additives, not only has stable properties throughout the entire synthesis process, but also does not introduce any impurities, has no effect on other materials or equipment, and plays an important role in improving consistency and batch stability; the pure-phase LATP seeds are the same as the final target product LATP solid electrolyte, do not incur any additional costs, and have an excellent cost-effectiveness ratio; the method directly sinters after mixing, has fewer processes and is easy to operate, and it can be seen that the scheme of the present invention is of great significance to the large-scale production and application of LATP solid electrolytes.

[0009] It should be noted that the pure phase LATP refers to a phase that only contains the phase corresponding to the standard PDF card #35-0754 and does not contain other phases.

[0010] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] As a preferred technical solution of the present invention, the mass of the pure phase LATP seed crystal accounts for 0.01% to 10.2% of the total mass of the lithium source, aluminum source, titanium source and phosphorus source, for example, it can be 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or 10.2%, etc.

[0012] It should be noted that pure phase LATP seed crystals as additives do not have side effects caused by excessive or insufficient amounts of other additives in the prior art. They only serve as nucleation seeds, so they can work as long as they are used. When they are in excess relative to other raw materials, there is only a problem of increased cost, and no impurities or pollution will be introduced.

[0013] As a preferred technical solution of the present invention, the method for preparing the pure phase LATP seed crystal includes: using a high-temperature electric spark sintering method, mixing a lithium source, an aluminum source, a titanium source and a phosphorus source, heating the mixture to 880-920°C within 20-40 minutes and treating the mixture for 20-40 minutes to obtain a pure phase LATP seed crystal; for example, the heating time can be 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, etc.; the treatment temperature can be 880°C, 890°C, 900°C, 910°C or 920°C, etc.; the treatment time can be 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, etc.

[0014] The present invention does not limit the method for preparing the pure phase LATP seed crystal to high temperature electric spark sintering, but it can quickly realize the preparation of high purity and high conductivity seed crystals in small batches. However, because this method has high requirements for equipment and high cost, it cannot meet the large-scale preparation of high purity, high conductivity, high dispersion and low cost LATP solid electrolyte products, but it is sufficient to meet the synthesis of small-sized pure phase LATP seed crystals.

[0015] Preferably, the particle size range of the pure phase LATP seed crystals is between 50 nm and 300 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm or 300 nm, etc.

[0016] As a preferred technical solution of the present invention, the method also includes adding an auxiliary agent for the mixing, wherein the auxiliary agent includes at least one of boron oxide, metaborate or fluoride; the mass of the auxiliary agent accounts for 0.01% to 50% of the total mass of the lithium source, aluminum source, titanium source and phosphorus source, for example, 0.01%, 0.05%, 0.08%, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48% or 50%, etc.

[0017] The present invention uses a low melting point auxiliary agent, which can melt into a liquid phase at a relatively low temperature, thereby promoting the contact between solid phase substances such as pure phase LATP seed crystals, lithium source, aluminum source, titanium source and phosphorus source, making the reaction more uniform and sufficient.

[0018] Preferably, the boron oxide includes boron trioxide, the metaborate includes lithium metaborate or lithium tetraborate; and the fluoride includes lithium fluoride.

[0019] As a preferred technical solution of the present invention, the mixing method is dry mixing, and the dry mixing time is 0 ~4h, for example, it can be 1min, 3min, 5min, 10min, 20min, 30min, 40min, 50min, 1h, 1.3h, 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h, 3h, 3.3h, 3.5h, 3.8h or 4h, etc.

[0020] Preferably, the equipment used for dry mixing includes at least one of an agate mortar, a small juicer, a Chinese medicine mixer, a ball mill, a V-shaped mixer or a high-speed mixer.

[0021] As a preferred technical solution of the present invention, the median particle size (i.e., particle size D 50 ) ranges from 10nm to 100μm, for example, 10nm, 30nm, 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 3μm, 5μm, 8μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm, etc.

[0022] Preferably, the lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium oxide.

[0023] Preferably, the aluminum source comprises aluminum oxide and / or aluminum hydroxide.

[0024] Preferably, the titanium source comprises titanium dioxide and / or titanate.

[0025] Preferably, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate or diammonium hydrogen phosphate.

[0026] Preferably, the mass of the lithium source is 1% to 50% in excess of the theoretical amount to supplement the volatilization of lithium during sintering, for example 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48% or 50%, etc.

[0027] It should be noted that the theoretical amount refers to the amount and ratio of the required lithium source, aluminum source, titanium source and phosphorus source calculated according to the chemical formula of the LATP solid electrolyte. The present invention does not limit the specific content of each component in the LATP solid electrolyte. The LATP solid electrolyte that has been widely studied and applied in the field can be prepared by the method described in the present invention. For example, a typical LATP chemical formula is Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0028] As a preferred technical solution of the present invention, the sintering temperature is 850-950°C, for example, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, and the sintering time is 2-6h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, etc.

[0029] As a preferred technical solution of the present invention, before the sintering, the mixed material is pre-burned to obtain a pre-burned material, and then the pre-burned material is sintered.

[0030] Preferably, the pre-firing temperature is 650-750°C, for example 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C or 750°C, and the pre-firing time is 2-6h, for example 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, etc.

[0031] As a preferred technical solution of the present invention, after the pre-burning and before the sintering, the obtained pre-burned material is crushed to obtain a crushed material; and then the crushed material is sintered.

[0032] It is worth noting that in the method of the present invention, the sintering can be directly performed after pre-sintering, which is equivalent to performing two stages of sintering treatment in succession, or the sintering can be performed after pulverizing and then sintering, which is equivalent to performing two sintering treatments respectively. In short, the purpose of adding pre-sintering and powder in the present invention is to further promote uniform contact of grains and consistent growth conditions, and further improve the uniformity and consistency of the obtained LATP solid electrolyte product.

[0033] Preferably, the equipment used for the pulverization includes at least one of a flat air flow pulverizer, a fluidized bed air flow pulverizer, a circulating air flow pulverizer, an impact crusher, an expansion crusher, a ball mill pulverizer, a high-speed rotating projectile pulverizer, a high-speed rotating impact pulverizer or a sand mill.

[0034] As a preferred technical solution of the present invention, after the sintering, the obtained LATP solid electrolyte is subjected to nano-treatment, and the median particle size of the product obtained after the nano-treatment ranges from 50nm to 500nm, for example, 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 230nm, 250nm, 280nm, 300nm, 330nm, 350nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm or 500nm, etc.

[0035] Preferably, the equipment used for the nano-processing includes at least one of a sand mill, a ball mill, a jet mill or a roller mill.

[0036] The purpose of the nano-processing in the present invention is to reduce the particle size of the LATP solid electrolyte to meet the needs of subsequent different applications.

[0037] In a second aspect, the present invention provides a LATP solid electrolyte, which is prepared according to the method described in the first aspect.

[0038] Preferably, the ionic conductivity of the LATP solid electrolyte is >0.5×10 -4 S / cm, after multiple batches of stability verification, the difference in ionic conductivity is within ±3%.

[0039] Preferably, the primary particle size span value (particle size distribution range value) of the LATP solid electrolyte is 1.0-1.2, and the secondary particle size span value is 1.2-1.6; span value = (particle size D 90 - Particle size D 10 ) / particle size D 50 .

[0040] It should be noted that due to space limitations and to avoid redundancy, the present invention does not exhaustively list all suitable values, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0041] Compared with the prior art solutions, the present invention has at least the following beneficial effects: The method of the present invention uses pure phase LATP as a "seed" for solid phase crystal growth during the mixing process to induce the raw materials to spontaneously form a pure phase LATP solid electrolyte, significantly reducing the content of impurity phases, improving the ionic conductivity and other properties of the solid electrolyte, and effectively improving consistency and batch stability. At the same time, the pure phase LATP seed crystal has the same composition as the target product when used as an additive, does not introduce any impurities, can remain consistent before and after sintering, and has no significant change in cost. Therefore, the self-induced crystal growth method has a high cost-effectiveness ratio and has great technical prospects in the large-scale production process of LATP solid electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the XRD diagram of the LATP solid electrolyte obtained in Example 1.

[0043] Figure 2 This is the EIS test graph of the LATP solid electrolyte obtained in Example 1.

[0044] Figure 3 This is the XRD diagram of the LATP solid electrolyte obtained in Example 6.

[0045] Figure 4 This is the EIS test graph of the LATP solid electrolyte obtained in Example 6.

[0046] Figure 5 This is the XRD diagram of the LATP solid electrolyte obtained in Comparative Example 1.

[0047] Figure 6 This is the EIS test graph of the LATP solid electrolyte obtained in Example 1.

[0048] Figure 7 This is the XRD diagram of the LATP solid electrolyte obtained in Comparative Example 2.

[0049] Figure 8 This is the EIS test graph of the LATP solid electrolyte obtained in Example 2. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0051] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention. Example 1

[0052] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, the method comprising: Preparation of pure phase LATP seed crystals, according to the chemical formula of LATP components is Li 1.3 Al 0.3 Ti 1.7 (PO4)3, weigh the raw materials, and control the lithium source to be in excess of 3%, specifically weigh 24.89g of lithium source lithium carbonate, 7.7g of aluminum source alumina, 67.9g of titanium source titanium dioxide and 172.5g of phosphorus source diammonium phosphate, and use high-temperature electric spark sintering to mix the lithium source, aluminum source, titanium source and phosphorus source, and then heat to 900°C within 30 minutes and treat for 30 minutes to obtain high-purity, high-performance pure-phase LATP seeds; multiple batches of preparation can be carried out to obtain sufficient pure-phase LATP seeds.

[0053] According to the chemical formula of LATP components, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 weigh the raw materials, and control the lithium source excess to 9.3%, specifically weigh 2640g of lithium source lithium carbonate, 770g of aluminum source alumina, 6790g of titanium source titanium dioxide, and 17250g of phosphorus source ammonium dihydrogen phosphate; relative to the above raw materials, weigh 279g of pure phase LATP seeds (1.02% by mass) and 420g of auxiliary agent boron trioxide (1.53% by mass), use a high-speed mixer to mix at high speed for 9 minutes, transfer to a sagger, load the raw materials into a sintering furnace, first heat to 700°C at 5°C / min and keep warm for 4h for pre-sintering, and then heat to 900°C at 3°C / min and keep warm for 4 hours to complete sintering to obtain a LATP solid electrolyte. Example 2

[0054] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, which adjusts the mass of pure phase LATP seed crystals from 279g to 27.9g, so that the mass proportion changes from 1.02% to 0.102%. Except for the above, other conditions are exactly the same as those in Example 1. Example 3

[0055] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, which adjusts the mass of pure phase LATP seed crystals from 279g to 1395g, so that the mass proportion changes from 1.02% to 5.10%. Except for the above, other conditions are exactly the same as those in Example 1. Example 4

[0056] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, which adjusts the mass of pure phase LATP seed crystals from 279g to 2790g, so that the mass proportion changes from 1.02% to 10.2%. Except for the above, other conditions are exactly the same as those in Example 1. Example 5

[0057] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte. The method does not perform the pre-sintering, but directly performs and completes the sintering at 900° C. Except for the above, other conditions are exactly the same as those in Example 4. Example 6

[0058] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, the method comprising: according to the chemical formula of LATP component Li 1.3 Al 0.3 Ti 1.7 (PO4)3 weigh the raw materials, and control the lithium source to be in excess of 9.3%, specifically weigh 2640g of lithium source lithium carbonate, 770g of aluminum source alumina, 6790g of titanium source titanium dioxide, and 1470g of phosphorus source concentrated phosphoric acid; relative to the above raw materials, weigh 279g of pure phase LATP seed (1.02% by mass) and 420g of auxiliary agent boron trioxide (1.53% by mass), use a high-speed mixer to mix the solid raw materials at high speed for 9 minutes, then add concentrated phosphoric acid to mix, and then transfer the mixture into a sintering furnace, first heat it to 700℃ at 5℃ / min and keep it warm for 4h to pre-sinter, and obtain a pre-sintered material; crush the pre-sintered material to obtain a crushed material; put the obtained crushed material into a bowl, put it into a sintering furnace, and then heat it to 900℃ at 3℃ / min and keep it warm for 4 hours to complete sintering, and obtain a LATP solid electrolyte. Example 7

[0059] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, which adjusts the mass of pure phase LATP seed crystals from 279g to 27.9g, so that the mass proportion changes from 1.02% to 0.102%. Except for the above, other conditions are exactly the same as those in Example 6. Example 8

[0060] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, which adjusts the mass of pure phase LATP seed crystals from 279g to 1395g, so that the mass proportion changes from 1.02% to 5.10%. Except for the above, other conditions are exactly the same as those in Example 6. Example 9

[0061] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, which adjusts the mass of pure phase LATP seed crystals from 279g to 2790g, so that the mass proportion changes from 1.02% to 10.2%. Except for the above, other conditions are exactly the same as those in Example 6. Example 10

[0062] This embodiment provides a method for self-induced crystal growth of LATP solid electrolyte, wherein the method does not perform the pulverization, and directly performs and completes the sintering after the pre-burning. Except for the above, other conditions are exactly the same as those of Example 9.

[0063] Comparative Example 1 This comparative example provides a method for synthesizing a LATP solid electrolyte, wherein the method does not use the pure phase LATP seed crystal. Except for the above, other conditions are exactly the same as those in Example 1.

[0064] Comparative Example 2 This comparative example provides a method for synthesizing a LATP solid electrolyte, wherein the method does not use the pure phase LATP seed crystal. Except for the above, other conditions are exactly the same as those in Example 6.

[0065] Characterization and Testing: Ⅰ. Phase of LATP material obtained by XRD test: Figure 1 , Figure 3 , Figure 5 and Figure 7 The XRD diagrams of the LATP solid electrolytes obtained in Example 1, Example 6, Comparative Example 1 and Comparative Example 2 are shown respectively. It can be seen from the diagram that after adding a small amount of seed crystals, a high-purity LATP solid electrolyte can be obtained; when no seed crystals are added, impurity phases often appear in the LATP electrolyte.

[0066] Ⅱ. Ionic conductivity test: Ionic conductivity is used to describe the ease of lithium ion transfer in solid electrolytes and is expressed by σ (unit: S / cm). During the test, the powder is die-cast into an electrolyte sheet at a certain pressure, and then the electrolyte sheet is sintered into a dense ceramic sheet. After gold spraying or brushing with conductive silver paste on both sides, an EIS test is performed using an electrochemical workstation to obtain its resistance value R, which is then calculated according to the formula σ=L / (R×S), where L is the thickness of the electrolyte sheet during the test (cm); S is the area of ​​the electrolyte sheet during the test (cm 2 ); Figure 2 , Figure 4 , Figure 6 and Figure 8The EIS test graphs of the LATP solid electrolytes obtained in Example 1, Example 6, Comparative Example 1 and Comparative Example 2 are shown in Figure 1. The resistance values ​​R are obtained from the graphs and then the ionic conductivities of the obtained LATP solid electrolytes are calculated to be 0.53×10 -4 S / cm, 0.50×10 -4 S / cm, 0.13×10 -4 S / cm and 0.42×10 -4 S / cm, and other results are recorded in Table 1.

[0067] Table 1

[0068] It can be seen from Table 1 that after adding LATP seed crystals, the ionic conductivity of the obtained LATP solid electrolyte is generally higher than 0.5*10 -4 S / cm, significantly better than the sample group of the comparative example, with obvious performance advantages. At the same time, it can be seen from Example 5 compared with Example 4 that the ionic conductivity of the LATP product obtained by direct one-time sintering after adding the seed crystal decreases, proving that two-stage sintering or two-stage sintering has a better effect on the synthesis of high-conductivity LATP electrolyte materials. At the same time, it can be seen from the comparison between Examples 1-4 or between Examples 6-9 that high-ionic-conductivity LATP electrolyte products can be obtained under different seed mass dosages.

[0069] In summary, the method of the present invention uses pure phase LATP as a "seed" for solid phase crystal growth during the mixing process, inducing the raw materials to spontaneously form a pure phase LATP solid electrolyte, significantly reducing the content of impurity phases, improving the ionic conductivity and other properties of the solid electrolyte, and effectively improving consistency and batch stability. At the same time, when the pure phase LATP seed is used as an additive, it has the same composition as the target product, does not introduce any impurities, can remain consistent before and after sintering, and has no significant change in cost. Therefore, the self-induced crystal growth method has a high cost-effectiveness ratio and has great technical prospects in the large-scale production process of LATP solid electrolytes.

[0070] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0071] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0072] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for self-induced crystal growth of LATP solid electrolyte, characterized in that: The method comprises: mixing pure phase LATP seed crystals, a lithium source, an aluminum source, a titanium source and a phosphorus source to obtain a mixed material; and sintering the obtained mixed material to obtain a LATP solid electrolyte.

2. The method for self-induced crystal growth of LATP solid electrolyte according to claim 1, characterized in that: The mass of the pure phase LATP seed crystal accounts for 0.01% to 10.2% of the total mass of the lithium source, aluminum source, titanium source and phosphorus source.

3. The method for self-induced crystal growth of LATP solid electrolyte according to claim 1 or 2, characterized in that: The method for preparing the pure phase LATP seed crystal comprises: using a high temperature electric spark sintering method, mixing a lithium source, an aluminum source, a titanium source and a phosphorus source, heating to 880-920° C. within 20-40 minutes and treating for 20-40 minutes to obtain a pure phase LATP seed crystal; The particle size of the pure phase LATP seed crystals ranges from 50 nm to 300 nm.

4. The method for self-induced crystal growth of LATP solid electrolyte according to claim 1, characterized in that: The method further includes adding an auxiliary agent for the mixing; the auxiliary agent includes at least one of boron oxide, metaborate or fluoride; the mass of the auxiliary agent accounts for 0.01% to 50% of the total mass of the lithium source, aluminum source, titanium source and phosphorus source.

5. The method for self-induced crystal growth of LATP solid electrolyte according to claim 1, characterized in that: The mixing method is dry mixing for 0.5 to 4 hours; the median particle size of the lithium source, aluminum source, titanium source and phosphorus source ranges from 10 nm to 100 μm; the mass of the lithium source exceeds the theoretical amount by 1% to 50%.

6. The method for self-induced crystal growth of LATP solid electrolyte according to claim 1, characterized in that: The sintering temperature is 850-950° C. and the sintering time is 2-6 hours.

7. The method for self-induced crystal growth of LATP solid electrolyte according to claim 1, characterized in that: Before the sintering, the mixed material is pre-fired to obtain a pre-fired material, and then the pre-fired material is sintered; the pre-fired temperature is 650-750° C. and the time is 2-6 hours.

8. The method for self-induced crystal growth of LATP solid electrolyte according to claim 7, characterized in that: After the pre-sintering and before the sintering, the pre-sintered material is crushed to obtain a crushed material; and then the crushed material is sintered.

9. The method for self-induced crystal growth of LATP solid electrolyte according to claim 1, characterized in that: After the sintering, the obtained LATP solid electrolyte is subjected to nano-processing, and the median particle size of the product obtained after the nano-processing is in the range of 50nm to 500nm.

10. A LATP solid electrolyte, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Solid-phase synthesis method for synthesizing garnet-structure lithium lanthanum zirconium oxygen solid electrolyte material under synergic effect of quaternary ammonium hydroxide

    CN110265708A

  • Preparation method of high-compaction lithium iron phosphate positive electrode material of lithium ion battery

    CN115806283A

  • LATP material as well as preparation method and application thereof

    CN118954467A

Cited By

  • Latp material prepared based on organic sodium salt template method and application thereof

    CN122599435A